2020
DOI: 10.1103/physrevb.101.220411
|View full text |Cite
|
Sign up to set email alerts
|

Observation of E8 particles in an Ising chain antiferromagnet

Abstract: Near the transverse-field induced quantum critical point of the Ising chain, an exotic dynamic spectrum consisting of exactly eight particles was predicted, which is uniquely described by an emergent quantum integrable field theory with the symmetry of the E8 Lie algebra, but rarely explored experimentally. Here we use high-resolution terahertz spectroscopy to resolve quantum spin dynamics of the quasi-one-dimensional Ising antiferromagnet BaCo2V2O8 in an applied transverse field. By comparing to an analytical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 35 publications
(20 reference statements)
8
48
0
2
Order By: Relevance
“…Motivated by these theoretical results, we experimentally revisited the spin dynamic spectrum in CoNb 2 O 6 by performing high-resolution terahertz spectroscopy in an applied transverse magnetic field. We identify not only the two lowest E 8 particles but also the higher-energy ones up to m 6 , as well as the peaklike maximum of the two-particle continuum (m 1 + m 2 ), confirming the theoretical predictions of the 1D quantum many-body system [17,35,36].…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Motivated by these theoretical results, we experimentally revisited the spin dynamic spectrum in CoNb 2 O 6 by performing high-resolution terahertz spectroscopy in an applied transverse magnetic field. We identify not only the two lowest E 8 particles but also the higher-energy ones up to m 6 , as well as the peaklike maximum of the two-particle continuum (m 1 + m 2 ), confirming the theoretical predictions of the 1D quantum many-body system [17,35,36].…”
Section: Introductionsupporting
confidence: 81%
“…Moreover, the two-particle continuum (m 1 + m 2 ) was found to be characterized by a peaklike maximum at the onset energy, and thus potentially resolvable on top of the (m 1 + m 1 ) continuum. Very recently the findings of the numerical simulations were supported by rigorous quantum field theory analysis of the dynamic spectra of the two-particle continua [35,36], which revealed that the spectral weight of the (m 1 + m 1 ) continuum decreases considerably with increasing energy, becoming relatively weak particularly at the energies where the higher-energy particles are predicted to appear. Moreover, it showed that the two-particle continua, such as (m 1 + m 1 ) and (m 1 + m 2 ), are not featureless but characterized by a peaklike maximum at the onset energies which is followed by an extended tail towards higher energies [35,36].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations